Framework for advancing water resource sustainability and climate resilience through local-scale hydrological modeling in the Mekong Delta - Matheswaran, Karthikeyan; Jampani, Mahesh; Sena, Dipaka Ranjan (International Water Management Institute (IWMI). CGIAR Initiative on Asian Mega-Deltas, 2023)
The Mekong Delta is a vast region that is crucial for providing food to millions of people. However, climate change and human activities are causing water scarcity, floods and soil salinization, which are a threat to food security and livelihoods. To tackle these issues, the CGIAR Initiative on Asian Mega-Deltas (AMD) is working towards creating more resilient, inclusive and productive deltas that can adapt to climate change and other challenges. As part of the AMD initiative’s activities, the International Water Management Institute (IWMI) is conducting local-scale hydrological modeling in two delta regions, namely Ganges and Mekong. This innovation brief outlines the methodology that will be used to develop satellite-based crop water use estimates for targeted irrigation schemes in the Mekong Delta. Through local partnerships, the AMD initiative hopes to generate site-specific knowledge that can be used to understand water use patterns, optimize water management at scales, increase agricultural productivity and ensure the long-term sustainability of this important deltaic system.